Living and community. - Mulgan, Geoff, ....- (London : Black Dog, 2008)
Do we live in a broken society, as claimed by both church leaders and politicians? Or, as Geoff Mulgan, a former head of the government's policy unit argues in this insightful book - are the bonds of community and place much stronger than acknowledged by the persistent doom-mongers? Mulgan suggests that there is everything to work for in local communities and that they are more than capable of being re-energised by new initiatives. As such, he proposes a new positive future for community life - if appropriate action is taken now.